Empowering Youth Through Sustainable Design: Community-Based Upcycling of Pine Forest Waste in Mekarwangi Village - Terbit Setya Pambudi; Nurul Fitriana Bahri; Oky Setiawan; Faradillah Nursari; Ica Ramawisari (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
Creative approaches rooted in local resources play an important role in sustainable community development. This community engagement program aimed to empower youth members of Community Youth Development in Mekarwangi Village, West Bandung Regency, through training in sustainable design using pine forest waste. Mekarwangi is surrounded by pine forests managed by Perhutani, which generate unused organic waste such as dry branches, bark, flowers, and sawdust. The program consisted of an environmental awareness session and practical workshops on upcycling techniques. Participants were introduced to the concept of sustainable design and guided through the process of transforming forest waste into functional and decorative crafts, including fish-shaped ornaments made from pine flower petals and leaves. The training emphasized the creative reuse of natural materials, while also promoting the principles of circular economy and environmental stewardship. As a result, participants developed new skills in material selection, product design, and simple craft production, which enhanced their confidence and awareness of environmental issues. The final products have potential as eco-friendly souvenirs, strengthening local identity and opening economic opportunities. This initiative demonstrated the role of design as a tool for grassroots empowerment, creativity, and sustainable community development.